The Good, the Bad, and the Ugly of Faith Healers and Psychiatric Illnesses: A Systematic Review of the Literature in the Arab World - Al Shelali, Musab (Journal of religion and health, 2024)
Faith healing is a traditional healing method involving spiritual and faith-based practices performed by a religious medicine man referred to here as a faith healer. The practice of faith healing is widespread in the Arab World for treating a range of mental disorders. This research aims to review the literature concerned with faith healing practice in the Muslim Arab population. Based on the results of the review, there are seven distinct aspects of faith healing. These include the characteristics of persons who visit faith healers, the rate of visits, the symptoms for which visits are made, the treatment methods, the general stigma and prevalent attitudes toward mental disorders in the Arab world, and the perceived effectiveness of faith healing as applied to mental disorders. The results of the review show that many patients with mental disorders, as a first resort, prefer to seek the help of faith healers (or other non-professional trusted counselors) rather than approach mental health services. This is due to several factors: the misconceptions around causes of mental illness in Arab traditions and culture and the stigma associated with mental illness. As an overall determination derived from the literature, Arabs remain highly reliant on faith healers as helpful resources for dealing with mental health problems. In conclusion, the recommendation to public health authorities is to consider including faith healers in the support system for mental health and cease viewing them as barriers to optimal care.